Growth and production performance of carps in shaded pond in Barisal, Bangladesh - Rumpa, RJ; Haque, MM; Alam, MM; Rahamatullah, SM (Journal of the Bangladesh Agricultural University, 2017)
The shaded nature of ponds in Barisal region constrained the pond polyculture. The present study was conducted with such shaded ponds to evaluate the growth and production performance of different carp species including rohu (Labeo rohita), catla (Catla catla), mrigal (Cirrhinus cirrhosus) and common carp (Cyprinus carpio) in polyculture system. In this experiment, polyculture of carps at similar densities were conducted in two different types of shaded ponds selecting nine ponds at Dinar village in Charkawa Union of Barisal Sadar sub-district. Out of 9 ponds, 5 were heavily shaded ponds (HSP) and 4 were moderately shaded ponds (MSP) considered as T1 and T2, respectively. The average area of HSP and MSP was 0.03±0.01 and 0.07±0.03 ha, respectively which were experimented for a period of l80 days from July to December 2013. Carps were stocked at the rate of 14820/ha with the ratio of rohu, catla, mrigal and common carp - 2:1:2:1. Carps were fed with supplementary feed of the mixture of rice bran, wheat bran and mustard oilcake at the rate of 10% body weight for first 3 months and 5% body weight for last 3 months. The water quality parameters such as temperature, dissolved oxygen, pH, nitrite and ammonia were recorded. The highest weight gain was found in common carp (467.00±0.00 g) in T1 and lowest weight gained in mrigal (172.46±26.80 g) in T1. Apart from common carp, the individual growth and production of other species was higher in MSP compared to HSP. The higher production was obtained in T2 (2122.92±333.60 kg/ha/year) compared to T1 (1547.79±132.94 kg/ha/year). J. Bangladesh Agril. Univ. 14(2): 235-241, December 2016